(untitled) (Al-Qamar, 2022)
Imam Fakhr al-Dīn al-Rāzī, Muslim theologian and scholar, universally acclaimed for his intellectual brilliance, and his extremely wide-ranging commentary on the Qur’an (Mafāṭīḥ al-Ghayb) which ranks among the greatest works of its kind -. Imam Razi’s rationalism holds an important place in the debate in the Islamic tradition on the harmonization of reason and revelation. Istidrāk means correction of mistake, completion of deficiency and clarification of ambiguity. Islamic sciences have a long tradition of this area of research. The present article studies the linguistic Istidrāks of Imam Fakhru al-Din al-Razi in his Tafsir (Mafāṭīḥ al-ghayb)on Qazi Abdul Jabbar al-mutzili. It concludes that these scholars have been objective while criticizing or differing with others. They very politely point out the mistakes of other scholars and try their best to guide their readers towards the accurate Islamic notions.